2005
DOI: 10.4103/0972-9941.16528
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy - Is there a need to convert?

Abstract: Introduction:The difficult gallbladder is the most common ‘difficult’ laparoscopic surgery being performed by general surgeons all over the world and the potential one that places the patient at significant risk. We present our experience of 6147 cases since January 1993 in a single center with respect to conversion to open cholecystectomy.Methods:Patients who underwent laparoscopic cholecystectomy (LC) from January 1993 to December 2004 were analyzed. The cases were analyzed in relation to conversion rate to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 9 publications
6
25
0
2
Order By: Relevance
“…Among the surgical causes, commonest difficulty encountered was frozen Calot's triangle with fibrosed thick walled gall bladder, seen in 92 patients (42 %), while insufficient insufflations due to gas leak was the commonest nonsurgical cause evident in 10 patients (35 %). Similar results have been in earlier studies [7,14,15]. Seventeen (8 %) patients with empyema gall bladder and the patient with Pott's paraplegia who had unresolved inflammation had difficult cholecystectomy.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Among the surgical causes, commonest difficulty encountered was frozen Calot's triangle with fibrosed thick walled gall bladder, seen in 92 patients (42 %), while insufficient insufflations due to gas leak was the commonest nonsurgical cause evident in 10 patients (35 %). Similar results have been in earlier studies [7,14,15]. Seventeen (8 %) patients with empyema gall bladder and the patient with Pott's paraplegia who had unresolved inflammation had difficult cholecystectomy.…”
Section: Discussionsupporting
confidence: 89%
“…Instead of defining "difficult" LC based only on clinico-anatomical situations, we had arbitrarily chosen a time frame for the same (1 h), since instrument failure in this series was an important factor not only prolonging surgery but was also detrimental to the safe completion of the laparoscopic procedure. The incidence of surgical causes of "difficult LC" in our study is similar to that reported in some other previous studies [14,15]. Among the surgical causes, commonest difficulty encountered was frozen Calot's triangle with fibrosed thick walled gall bladder, seen in 92 patients (42 %), while insufficient insufflations due to gas leak was the commonest nonsurgical cause evident in 10 patients (35 %).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Signs of acute cholecystitis were investigated by authors either with clinical signs or laboratory parameters like WBC count. 1,3,4,7,11,13,14 Constantini et al found that a WBC count of greater than 9000 had a statistically significant correlation with conversion whereas Nidoni et al mentioned counts more than 11000 as significant in his study. 1,7 Clinical signs of cholecystitis like pain and fever were found to be significant in prediction of difficulty by all authors, except in study by Constantini et al, where only the elevated WBC count was significant.…”
Section: Clinical Parameters-disease Factorsmentioning
confidence: 85%
“…[16][17][18][19] As was suggested by Hunter " to get it while its hot" 20 , the safety and feasibility of laparoscopic cholecystectomy has been pushed to its limits as more and more surgeons are performing them in acute cholecystitis. Very few studies have reported its safety profile in Empyema Gall Bladder.…”
Section: Discussion:-mentioning
confidence: 99%